Monitoring healthcare improvement for mothers and newborns: A quantitative review of WHO/UNICEF/UNFPA standards using Every Mother Every Newborn assessment tools - Siseho, Gloria Mutimbwa; Mathole, Thubelihle; Jackson, Debra (Frontiers in Pediatrics, 2022)
Background: Assessment tools with the ability to capture WHO/UNICEF/UNFPA standard quality of care measures are needed. This paper aims to assess the ability of the Every Mother Every Newborn (EMEN) tools to capture the WHO/UNICEF/UNFPA maternal newborn quality improvement standard indicators. Methods: A quantitative study using the EMEN quality assessment framework was applied. The six EMEN tools were compared to the WHO/UNICEF/UNFPA maternal and newborn quality improvement standards. Descriptive statistics analysis was done, with summaries using tables and figures. Results: Overall, across all EMEN tools 100% (164 of 164) input, 94% (103 of 110) output and 97% (76 of 78) outcome measures were assessed. Standard 2 measures, i.e., actionable information systems, were 100% (17 of 17) completely assessed by the management interview, with 72% to 96% of standard 4-6 measures, i.e., client experiences of care, fulfilled by exit interview tool. Conclusion: The EMEN tools can reasonably measure WHO/UNICEF/UNFPA quality standards. There was high capacity of the tools to capture enabling policy environment and experiences of care measures not generally covered in other available tools which are used to measure quality of care.